COMPARATIVE ANALYSIS AND COLLABORATIVE INNOVATION OF PARAMETRIC GENERATION AND AIGC - LIU, WEI; BEZUHLA , R. (Art and Design, 2024)
Purpose. The purpose of the article is to conduct a comparative analysis of the characteristic features, advantages, and limitations of parametric design and AIGC in the context of potential opportunities for joint innovation and achieving synergistic effects. Methodology. The theoretical and methodological basis of the study was formed by such general scientific approaches as comparative and systemic approaches, which made it possible to carry out a comparative analysis of parametric design and AIGC and to imagine their integrity; the structural-functional approach made it possible to analyze the patterns and principles of the functioning of parametric design and AIGC in the context of potential opportunities for joint innovations. Results. The study results have theoretical and practical significance, which consists of expanding the application of parametric generation and artificial intelligence in design, focusing on their functional characteristics and areas of application. A comparative analysis of parametric design and artificial intelligence was carried out through technical principles, tools, generation stages, designer involvement, aesthetics, and creativity, and their features, strengths, and limitations were analyzed. Approaches such as transitioning from parametric design to artificial intelligence were proposed to achieve a synergistic effect. It was emphasized that parametric design can stimulate the creation of artificial intelligence. In contrast, artificial intelligence can help in conceptual design, obtain parameters, support parametric models, and serve as input data for parametric models. It was found that artificial intelligence can also evaluate and refine parametric generation results. It is concluded that parametric design and artificial intelligence complement each other, have significant potential for joint innovations in the design field, and their simultaneous use allows for a synergistic effect. Scientific novelty. The article conducts a comprehensive comparative study of the parametric generation and AIGC technologies from various perspectives, including technical principles, design tools, different stages of the generation process, the role and participation of designers, aesthetics, and creativity. It identifies the strengths and corresponding limitations of parametric modeling and AIGC and proposes new approaches to their use in the field of design and achieving a synergistic effect. Practical significance. The results obtained lead to a deeper understanding of such modern phenomena as parametric generation and AIGC, which allowed us to develop practical recommendations for their systematic use in the field of design, for the development of new design tools and design processes.